Joint mobilization for frozen shoulder: A protocol for systematic review and meta-analysis. Issue 14 (8th April 2022) - Yao, Junjie; Liu, Chang; Pang, Tingting; Li, Jiahui; Lei, Siyuan; Zhang, Jiangchun; Wang, Yufeng; Shang, Qiangqiang
Abstract: Background: The purpose of this study was to evaluate the effectiveness and safety of Joint mobilization in the treatment of frozen shoulder. Methods: To collect relevant literature, we will research following databases: Medicine, PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wan-Fang Database, Chongqing VIP Chinese Science and Technology Periodicaols Database, and China Biomedical Database; the time is from its creation to May 2021, and the language is limited to Chinese and English. In addition, we will retrieve other literature resources, including the Chinese Clinical Trial Register and conference articles. Two reviewers will independently complete the literature screen and data extraction and quality assessment of the included studies will be independently completed by 2 other researchers. The primary outcomes included joint ROM and Japanese Orthopedic Association score. Visual Analogue Scale score, Activities of Daily Living score and adverse reactions as secondary outcomes were assessed. RevMan V.5.4.1 software will be used for meta-analysis, and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) will be used to assess the quality of evidence. Results: This systematic review will provide a high-quality synthesis to evaluate the efficacy and safety of joint mobilization in the treatment of frozen shoulder, providing a reference for the safe and effective treatment of frozen shoulder. Conclusion: This study provides evidence that joint mobilization in the treatment of frozen shoulder is effective. Ethics and dissemination: The protocol of the systematic review does not require ethical approval because it does not involve humans. This article will be published in peer-reviewed journals and presented at relevant conferences. Systematic review registration: INPLASY202210075